Surface energy and wettability control in bio-inspired PEG like thin films - Amjed Javid (2018)
© 2015 Elsevier Ltd. Tailoring of chemical functionalities in polymer films can induce interesting biocompatibility, however the sequential process of polymerization followed by functionalization imposes surface-interface complexities and inhomogeneity of functional groups across the thickness. Here, a single-step plasma process, enabling the simultaneous polymerization-functionalization, is demonstrated to control the surface energy and wettability of polyethylene glycol-like thin films. Chemical studies, carried out by Fourier transform infra-red spectroscopy and X-ray photoelectron spectroscopy, confirm the evolution and enhancement in amide functionalities, owing to the increase in the electronic transitions related to nitrogen based ions/radicals (independently confirmed by optical emission spectroscopy). In present case, the evolution and control over amide functionalities lead to the enhancement in wettability and surface energy tailoring in 60.5-67.5mJ/m2range. Excellent growth of L-929 fibroblast cells is obtained by the synergic contribution of plasma power and N2flow rate via enriching the amide functionalities in these films.